On the solution of energy balance equation system to predict temperature distribution in the building elements with ventilated air gap - Monstvilas, Edmundas; Banionis, Karolis; Poderytė, Jurga; Bliūdžius, Raimondas; Burlingis, Arūnas (Journal of Civil Engineering and Management, 2014)
The article presents the solution of heat balance equation system, describing heat exchange processes in ventilated envelopes, which was applied to derive formulas for the calculation of temperatures in the ventilated layers of the envelopes. The accurateness of the formulas was assessed by experimental research and analysis of the calculation results. During the process of heat exchange balance equation solution, the equations were simplified by introducing the following restriction into the derived formulas: they may only be applied for the ventilated envelopes with steel or similar coatings as their external layers, i.e. coatings having small heat capacity and minor difference between the external and internal surface temperatures. The derived formulas enable the calculation of the temperatures of the ventilated envelopes in the distance which does not exceed a half of the ventilated air gap length measuring from the air entrance into the gap. However, this restriction does not impede the estimation of the average thermal indicators of the ventilated envelopes.